Art and identity in thirteenth-century Byzantium - Eastmond, Antony, 1966- (My University, 2004)
The church of Hagia Sophia in Trebizond, built by the emperor Manuel I Grand Komnenos (1238-63) in the aftermath of the fall of Constantinople to the Fourth Crusade, is the finest surviving Byzantine imperial monument of its period. Antony Eastmond examines the architectural, sculptural and painted decorations of the church, placing them in the context of contemporary developments elsewhere in the Byzantine world, in Seljuq Anatolia and among the Caucasian neighbours of Trebizond
Hagia Sophia and the empire of Trebizond
Antony Eastmond.- Aldershot, Hants, England ; Burlington, VT : Ashgate/Variorum, 2004.- xxi, 208 p., [16] p. of plates : ill. (some col.), maps ; 26 cm.- Includes bibliographical references (p. [159]-199) and index
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ՖԲ Library of Byzantine Studies կայքից
https://mamlikshistory.blogspot.com/2023/03/download-pdf-art-and-identity-in.html
Keywords: Ayasofya Müzesi (Museum: Trabzon, Turkey); Architecture, Byzantine-Turkey-Trabzon; Christian art and symbolism-Turkey-Trabzon-Medieval, 500-1500; Art and state-Turkey-Trabzon; Trebizond Empire-History